Branching out with filmless radiology...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Carbajal R; Honea R (Journal of Digital Imaging)
Texas Children's Hospital, a 456 bed pediatric hospital located in the Texas Medical Center, has been constructing a large-scale picture archiving and communications system (PACS), including ultrasound (US), computed tomography (CT), magnetic resonance (MR), and computed radiography (CR). Until recently, filmless radiology operations have been confined to the imaging department, the outpatient treatment center, and the emergency center. As filmless services expand to other clinical services, the PACS staff must engage each service in a dialog to determine the appropriate level of support required. The number and type of image examinations, the use of multiple modalities and comparison examinations, and the relationship between viewing and direct patient care activities have a bearing on the number and type of display stations provided. Some of the information about customer services is contained in documentation already maintained by the imaging department. For example, by a custom report from the radiology information system (RIS), we were able to determine the number and type of examinations ordered by each referring physician for the previous 6 months. By compiling these by clinical service, we were able to determine our biggest customers by examination type and volume. Another custom report was used to determine who was requesting old examinations from the film library. More information about imaging usage was gathered by means of a questionnaire. Some customers view images only where patients are also seen, while some services view images independently from the patient. Some services use their conference rooms for critical image viewing such as treatment planning. Additional information was gained from geographical surveys of where films are currently produced, delivered by the film library, and viewed. In some areas, available space dictates the type and configuration of display station that can be used. Active participation in the decision process by the clinical service is a key element to successful filmless operations. Copyright (c) 1999 by W.B. Saunders Company